Cessation of ice-wedge development during the 20th century in spruce forests of eastern Mackenzie Delta, Northwest Territories, Canada - Kokelj, S V; Pisaric, M FJ; Burn, C R (Canadian Journal of Earth Sciences, 2007)
Ice wedges are presently inactive in white spruce (Picea glauca) forests of eastern Mackenzie Delta as shown by the absence of vein ice above ice wedges, the maintenance of intact breaking cables, and the abundance of rootlets propagating across ridge–trough sequences. At spruce forest sites, near-surface ground cooling rates and minimum near-surface temperatures from the years 2003–2005 were above ice-wedge cracking thresholds. Ground thermal conditions associated with cracking were recorded at a tundra peatland with active ice wedges. Annual mean permafrost temperatures at the spruce forest sites ranged from –1.8 to –2.9 °C, whereas at the tundra peatland, the permafrost was colder than –6 °C. Although winter air temperatures are similar throughout the study region, deeper snow cover, thicker active layers, and warmer permafrost account for the more gradual seasonal cooling and warmer near-surface temperatures recorded at the subarctic forest sites. The subtle ridge to trough relief, 12–35 cm of permafrost above wedge ice, roots up to 80 years old grown across ice wedges, and negligible tritium levels in wedge ice indicate that thermal contraction cracking in the spruce forests has been infrequent throughout much of the last century. The proximity of wedge ice to the base of the aggrading permafrost table and the absence of old spruce roots spanning ice-wedge troughs suggest that ice-wedge cracking did occur in the forest environments during the cold and dry conditions associated with the Little Ice Age and early part of the 20th century. When these ice wedges cracked, minimum temperatures at the top of permafrost were probably at least 3–8 °C colder than presently observed and similar to present conditions at the tundra peatland.